THE EFFECT OF CONCENTRATION AND TIME VARIATION OF THE LACTOSE AND SKIM MILK AS INDUCER ON THE EXPRESSION OF RECOMBINANT PROTEIN BOVINE LACTOFERRIN CARBOXY-TERMINUS (BLF CAR) - Febriyan Muji Hartini; I Gusti Ngurah Kade Mahardika; I Wayan Masa Tenaya (Buletin Veteriner Udayana, 2026)
Recombinant bovine lactoferrin (bLf) production has broad potential applications in animal health, particularly as a feed additive and immunomodulatory agent, thereby requiring an efficient and sustainable production system. Lac operon–based expression systems commonly employ isopropyl β-D-1-thiogalactopyranoside (IPTG) as an inducer; however, its high cost and potential to induce metabolic stress limit its applicability for large-scale production. This study aimed to evaluate lactose and skim milk as alternative inducers for recombinant bLf expression. A synthetic bLf CAR gene was cloned into the pGEX-2TK plasmid to generate a GST-bLf CAR fusion protein and expressed under a lac operon–based system. Induction was performed using lactose and skim milk at concentrations of 1%, 2.5%, and 5%, with induction times of 5, 24, and 48 hours, while 0.1 mM IPTG served as the reference inducer. The experimental design followed a randomized block design. Protein expression was analyzed using dot blot, and signal intensity was quantified using ImageJ software. Statistical analysis was conducted using two-way ANOVA followed by Tukey ’s post hoc test. The results demonstrated that inducer type, concentration, and induction time significantly affected the expression intensity of recombinant GST-bLf CAR protein (p < 0.01). Skim milk at a concentration of 2.5% with a 5 hour induction period produced the highest expression level and differed significantly from other treatments. These findings indicate that skim milk is a promising, economical, and practical alternative inducer for recombinant bLf production.